Mikrobioma Kulit dan Peran Probiotik Pada Dermatitis Atopik - Sonya Ananda Ellya John; Muhammad fahmi Tamami; Dedianto Hidajat (Faculty of Medicine Universitas Mataram, 2022)
Abstract Atopic dermatitis (AD) is a multifactorial inflammatory skin disease that has a high prevalence globally. Many underlying factors can be the occurrence of AD, one of which is an imbalance in the composition and diversity of the microbiome in the skin and gut or it can be called a condition of dysbiosis. Management and prevention of dysbiosis can be a treatment strategy in AD. Various studies have been conducted to see the effectiveness of using biotic products, such as probiotics, in the management strategy of AD. Based on available scientific evidence, this review discusses skin microbiome and the role of probiotics in AD. Keywords: atopic dermatitis, dysbiosis, microbiome, probiotic 1Medical Doctor Profession Education Program Faculty of Medicine University of Mataram 2Dermatovenereology Department, Faculty of Medicine University of Mataram / West Nusa Tenggara General Provincial Hospital Email : sonyaaej@gmail.com